Responding to Other People’s Posture: Visually Induced Motion Sickness From Naturally Generated Optic Flow - Cook, Henry E.; Hassebrock, Justin A.; Smart, L. James (Frontiers in Psychology, 2018)
Understanding the relationship between our actions and the perceptual information that is used to support them is becoming increasingly necessary as we utilize more digital and virtual technologies in our lives. Smart and his colleagues (2014) found that altering the relationship between perception and action can have adverse effects, particularly if the perceptual information cannot be used to guide behavior. They also found that motion characteristics varied between people who remained well and those that became motion sick. The purpose of this study was to determine the influence of naturally produced virtual motion on postural regulation and examine how people respond to different types of optical flow (produced by other people). Participants were either exposed to optic flow produced by the postural motion of a person who did not become motion sick, or a person who did exhibit motion sickness from Smart and his colleagues (2014). It was discovered that participants exhibited both stronger coupling and more incidents of motion sickness in response to optic flow generated by a non-sick participant. This suggests that participants recognized the potentially usable nature of the well-produced optic flow- but the open loop nature of the stimuli made this perception disruptive rather than facilitative.